Randomized Trial of Intravenous Versus Intraperitoneal Chemotherapy Plus Bevacizumab in Advanced Ovarian Carcinoma: An NRG Oncology/Gynecologic Oncology Group Study - Walker, Joan L; Brady, Mark F; Wenzel, Lari; Fleming, Gini F; Huang, Helen Q; DiSilvestro, Paul A; Fujiwara, Keiichi; Alberts, David S; Zheng, Wenxin; Tewari, Krishnansu S; Cohn, David E; Powell, Matthew A; et al. (Journal of clinical oncology, 2019)
To evaluate the impact of two different intraperitoneal (IP) chemotherapy regimens on progression-free survival (PFS) among women with newly diagnosed advanced ovarian carcinoma. Eligible patients were randomly assigned to six cycles of IV paclitaxel 80 mg/m once per week with intravenous (IV) carboplatin area under the curve 6 (IV carboplatin) versus IV paclitaxel 80 mg/m once per week with IP carboplatin area under the curve 6 (IP carboplatin) versus once every 3 weeks IV paclitaxel 135 mg/m over 3 hours day 1, IP cisplatin 75 mg/m day 2, and IP paclitaxel 60 mg/m day 8 (IP cisplatin). All participants received bevacizumab 15 mg/kg IV every 3 weeks in cycles 2 to 22. A total of 1,560 participants were enrolled and had 84.8 months of follow-up. The median PFS duration was 24.9 months in the IV carboplatin arm, 27.4 months in the IP carboplatin arm, and 26.2 months in the IP cisplatin arm. For the subgroup of 1,380 patients with stage II/III and residual disease of 1 cm or less, median PFS was 26.9 (IV-carboplatin), 28.7 (IP-carboplatin), and 27.8 months (IP cisplatin), respectively. Median PFS for patients with stage II/III and no residual disease was 35.9, 38.8, and 35.5 months, respectively. Median overall survival for all enrolled was 75.5, 78.9, and 72.9 months, respectively, and median overall survival for stage II/III with no gross residual disease was 98.8 months, 104.8 months, and not reached. Mean patient-reported Functional Assessment of Cancer Therapy neurotoxicity scores (Gynecologic Oncology Group) were similar for all arms, but the mean Trial Outcome Index of the Functional Assessment of Cancer Therapy-Ovary scores during chemotherapy were statistically worse in the IP cisplatin arm. Compared with the IV carboplatin reference arm, the duration of PFS was not significantly increased with either IP regimen when combined with bevacizumab and was better tolerated than IP cisplatin.